2011
DOI: 10.1503/cjs.044209
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of diabetes mellitus by ileal transposition compared with biliopancreatic diversion in a nonobese animal model of type 2 diabetes

Abstract: Background: It has been demonstrated that biliopancreatic diversion (BPD) and ileal transposition (IT) effectively induce weight loss and long-term control of type 2 diabetes in morbidly obese individuals. It is unknown whether the control of diabetes is better after IT or after BPD. The objective of this study was to investigate the effects of IT and BPD on the control of diabetes in an animal model. Methods:We performed IT and BPD on 10-to 12-week-old Goto-Kakizaki rats with a spontaneous nonobese model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In fact, previous investigations in rodents suggest that elevation of GLP-1 levels may be a late phenomenon after DJB (13)(14)(15)39,40).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, previous investigations in rodents suggest that elevation of GLP-1 levels may be a late phenomenon after DJB (13)(14)(15)39,40).…”
Section: Discussionmentioning
confidence: 98%
“…The concept of ileal transposition (IT) was first described in rodent experiments [3]. It has been confirmed that ileal transposition can improve glucose tolerance compared with other bariatric surgeries, was faster to perform, and yielded a shorter recovery time in animal models of non-obese type 2 diabetes [4,5]. These findings strongly suggested that an underlying hormonal mechanism involving the terminal ileum may participate in the resolution of type 2 diabetes after surgery [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…A similar reduction of weight increase during the first weeks after IIP and sham surgery has been described for rats on standard diet with low-dose STZ-induced diabetes [ 41 ] and for a genetic type 2 diabetes mellitus rat model [ 48 ]. However, in these experiments, a reduction of body weight after IIP surgery compared to sham surgery was clearly evident after longer postsurgery periods [ 12 , 26 , 29 , 30 , 37 , 38 , 40 , 41 , 43 , 44 , 46 , 47 , 58 , 62 ].…”
Section: Resultsmentioning
confidence: 80%
“…The data show that IIP surgery improved glucose tolerance and insulin sensitivity in rats with T2LD. Improved glucose tolerance and insulin sensitivity following IIP surgery have been previously reported in two nonobese genetic diabetic models: the Goto-Kakizaki-rats [ 13 , 26 , 38 , 39 ] and the Zucker rats [ 47 ].…”
Section: Resultsmentioning
confidence: 94%